(untitled) (Research, Society and Development, 2021)
This article sought to analyze how the activists of the Union of Women of São Paulo understand the guarantee of the right to women’s health from Primary Health Care. For this study, the qualitative method was used, based on semi-structured interviews with three militants of the Non-Governmental Organization Union of Women, in the city of São Paulo. The interviews were analyzed using Bardin’s content analysis technique. Of the empirical material produced, they were worked as part of the category of analysis: barrier in access to health. Women know and militate about access to rights, because two of them participated in the Construction of the Comprehensive Health Care Program for Women (PAISM). They point to weaknesses in the system to be worked from the perspective of humanization to guarantee women’s rights. It is necessary to revisit the daily practices of health professionals in the care of women, to identify and combat prejudices and moral judgments that deny rights, besides negatively impacting women’s lives.